Cognitive control functions in individuals with obesity with and without binge‐eating disorder. Issue 3 (12th January 2018) - Kollei, Ines; Rustemeier, Martina; Schroeder, Stefanie; Jongen, Sebastian; Herpertz, Stephan; Loeber, Sabine
Abstract: Objective: Deficits in cognitive control are thought to contribute to the maintenance of obesity (OB). Cognitive control is referred to as impulsivity and binge‐eating disorder (BED) is characterized by high levels of impulsivity. The present study sought to elucidate which cognitive control functions differentiate between severe OB with and without BED also taking into account hunger as a moderating factor. Method: The study included 48 individuals with OB and BED (OB + BED), 48 individuals with OB and no BED (OB – BED) and 48 normal‐weight controls (NWC). Hunger was systematically manipulated: participants were instructed to refrain from eating before testing and received either a liquid meal or flavored water. Then, a comprehensive test battery was administered including a food‐related go/no‐go task and several subtests from the CANTAB. Results: There were no differences between the groups with regard to food‐related response inhibition. However, while manipulating hunger had no impact on performance in the go/no‐go task, self‐reported hunger significantly influenced task performance by increasing inhibition deficits to high‐caloric stimuli in OB + BED. With regard to general cognitive control functions, we found that deficits in attention and impulse control in decision‐making distinguished OB from NWC, while reversal learning and risk taking in decision‐making appeared to be relevant factors when distinguishing OB + BED from OB − BED. Discussion: Our results indicate that self‐reported hunger differentially affected food‐related response inhibition. Group differences in general cognitive control functions were limited to attention, reversal learning, and decision‐making. Future research needs to account for other possible moderating factors, such as mood, food craving, or stress.